Trade effects of monetary integration in large, mature economies: a primer on the European Monetary Union - Lúcio Vinhas de Souza (Kiel Institute for World Economics (IfW), 2002)
The aim of this paper is to estimate the trade gains arising from the constitution ofa currency union for a set of economically large, developed nations who create a monetary union as a deliberate economic policy action: namely, for the members of the euro area. With a 1980-2001 sample, no consistent significant trade effects from the 1999 creation of EMU are found, using dummies for the 1999-2001 period. Treating EMU not as a single event but as a part of a long-term integration process, and representing it by a series of continuous cross-country interest differentials, the evidence seems to be stronger, but it does not seem to be conditional on any single, specific exchange rate arrangement.
Keywords: 330; Currency Unions; EU; EMU; panel model; gravity equation; Europäische Wirtschafts- und Währungsunion; Wirtschaftsintegration; Außenhandelseffekt; Gravitationsmodell; Schätzung; EU-Staaten